‘Race’, ‘Nation’, ‘People’: Ethnic Identity-Construction in 1 Peter 2 - Horrell, David G. 1963- (2012)
1 Peter 2.4–10 is a significant passage within the letter, rich in material from the Jewish scriptures. Verse 9 is particularly significant for the construction of Christian group-identity in that it uniquely applies three words from the vocabulary of ethnic identity to the Church: γένος, ἔθνος, and λαός, widely translated as ‘race’, ‘nation’, and ‘people’. A survey of these words in pre-Christian Jewish literature (especially the LXX), in the NT, and in other early Christian literature, reveals how crucial this text in 1 Peter is to the process by which Christian identity came to be conceived in ethnoracial terms. Drawing on modern definitions of ethnic identity, and ancient evidence concerning the fluidity of ethnic identities, it becomes clear that ‘ethnic’ and ‘racial’ identities are constructed, believed, and sustained through discourse. 1 Peter, with both aggregative and oppositional modes of ethnic reasoning, makes a crucial contribution to the construction of an ethnic form of Christian identity.
Keywords: 1 Peter; Christian Identity; Race; Ethnicity